Results of treatment of primary staphylococcal enterocolitis in infants with the use of antibacterial drugs and their combination with bacteriophages: a prospective study - O. G. Kimirilova; G. A. Kharchenko (LLC "Diagnostics and Vaccines", 2021)
In infectious pathology in infants, staphylococcal infection occupies a leading place, is characterized by the rapid development of intoxication, a purulent-destructive process with the possibility of generalization of infection, affecting the course and outcome of the disease.The aim of the study was to study the results of treatment of primary staphylococcal enterocolitis, in infants, with the use of antibacterial drugs and their combination with bacteriophages.Research methods. The frequency of elimination of staphylococcus, the duration of the main symptoms (fever, diarrhea, toxicosis with exicosis) as a result of treatment of primary staphylococcal enterocolitis (confirmed by laboratory) were analyzed in children aged from 1 to 12 months who received inpatient antibacterial drugs (nifuroxazide, azithromycin) or their combination with bacteriophages (staphylococcal, pyobacteriophage). The data accounting period is from January 2017 to December 2020.The results of the study. The results of treatment of staphylococcal enterocolitis were studied in 4 groups: monotherapy with nifuroxazide (n = 39) or azithromycin (n = 40), a combination of nifroxazide+staphylococcal bacteriophage (n = 41) or azithromycin + piobacteriphage (n = 38). The groups were comparable by gender, age, and clinical manifestations of the disease. Elimination of staphylococcus on the 10th-12th day. treatment with monotherapy with antibacterial drugs was achieved in 31-35%, with their combination with bacteriophages - in 51-64% of patients in each combination (df = 3, p < 0.05). Against the background of combined therapy, the symptoms of the disease (diarrhea, vomiting) were stopped 1.2 times faster; the number of patients with lactase deficiency and intestinal dysbiosis decreased by 1.7-2 times, with monotherapy with antibacterial drugs-by 1.3-1.4 times (df = 3, p < 0.05).Conclusion. Treatment of primary staphylococcal enterocolitis in children, including antibacterial drugs and bacteriophages, is more effective than monotherapy with antibacterial drugs.